Development of Interactive Physics E-Modules Based on Guided Inquiry on the Material of the Nature of Physics and Occupational Safety for High School Students - Sampe Hamongan Turnip; Tugiyo Aminoto; Suharli A. J (Mataram University, 2026)
The advancement of digital technology in education demands the availability of teaching materials that facilitate independent, interactive, and student-centered learning. In line with the implementation of the Independent Curriculum, the use of digital learning media is an alternative to increase student engagement in the physics learning process, which has traditionally been considered abstract and difficult to understand. This study aims to develop an interactive physics e-module based on guided inquiry on the Nature of Physics and Occupational Safety and to determine its level of validity, practicality, and effectiveness. The study used the Research and Development (R&D) method with a 4D model that includes the define, design, develop, and disseminate stages. The study was conducted at SMA Negeri 8 Jambi City with 35 students of grade X Phase E as subjects. The research instruments were validation sheets from material experts and media experts, questionnaires on teacher and student practicality, and questionnaires on student effectiveness. Data were analyzed descriptively quantitatively using percentages. The results showed that the e-module obtained a very good level of validity with a percentage of validation from material experts of 81.95% and media experts of 89.00%. The practicality level obtained a percentage of 94.7% based on teacher assessments and 87.3% based on student assessments. The effectiveness level reached 89.3%. These results indicate that the interactive physics e-module based on guided inquiry developed meets the criteria of validity, practicality, and effectiveness, making it suitable for use as a learning medium to support the implementation of the Independent Curriculum